An Intrinsically Self‐Healing NiCo||Zn Rechargeable Battery with a Self‐Healable Ferric‐Ion‐Crosslinking Sodium Polyacrylate Hydrogel Electrolyte. Issue 31 (5th July 2018) - Huang, Yan; Liu, Jie; Wang, Jiaqi; Hu, Mengmeng; Mo, Funian; Liang, Guojin; Zhi, Chunyi
Abstract: Self‐healing solid‐state aqueous rechargeable NiCo||Zn batteries are inherently safe and have a high energy density and mechanical robustness. However, the self‐healability of solid‐state batteries has only been realized by a few studies in which electron/ion‐inactive self‐healable substrates are utilized. This arises from the lack of self‐healable electrolytes. Now an intrinsically self‐healing battery has been designed that utilizes a new electrolyte that is intrinsically self‐healable. Sodium polyacrylate hydrogel chains are crosslinked by ferric ions to promote dynamic reconstruction of an integral network. These non‐covalent crosslinkers can form ionic bonds to reconnect damaged surfaces when the hydrogel is cut off, providing an ultimate solution to the intrinsic self‐healability problem of batteries. As a result, this NiCo||Zn battery with this hydrogel electrolyte can be autonomically self‐healed with over 87 % of capacity retained after 4 cycles of breaking/healing. Abstract : Electrolyte healing : A ferric‐ion‐crosslinking sodium polyacrylate hydrogel electrolyte furnishes a NiCo||Zn battery with unprecedented intrinsic self‐healing ability (over 87 % of capacity retained after 4 cycles of breaking/healing). It also has few components and a facile fabrication.